The Use of Code Switching in General English Classes for Non-English Department Students in Indonesia - Thomas Wahyu Prabowo Mukti; Ouda Teda Ena (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
The issue of the use of code switching as instructional languages in the class has already become a worldwide concern. Some experts may say that it is beneficial while others believe that it is not since it may become the interference for the learning. Through this paper, the researchers want to investigate the use of code switching in General English Classes for non-English Department of Sanata Dharma University. Employing a quantitative approach, specifically observation method by recording the class activity, this study tries to find out the types and analyse code switching employed by lecturers in the classes. The data analyses revealed that tag switching, intra-sentential and inter-sentential code switching are employed by lecturers and the code switching itself functions as the topic switch, repetitive and affective function. The inter-sentential code switching was mostly used by the lecturer and it mostly served as a repetitive function to explain and show their affection to students